Multi-objective Topology Optimization of Sandwich Lattice Structures for Vibration Suppression: Numerical and Experimental Investigations - Liu, Xu-Sheng; He, Meng-Xin; Ding, Qian (Journal of Vibration Engineering & Technologies, 2024)
Purpose Lattice structures have great potential in lightweight design, high structural strength, and vibration control. In this study, we investigate the multi-objective topology optimization of lattice structures, considering the static and vibroacoustic properties simultaneously. The sandwich lattice structure was subject to an eccentric rotating mass vibration motor, which offers dynamic loads. The aim is to minimize the static compliance and structure-borne noise, which leads to the multi-objective optimization problem (MOP). Methods We applied the bi-directional evolutionary optimization algorithm and the linear scalarization scheme to handle the MOP design of lattice structures. To improve the optimization efficiency, we utilized the mix displacement/pressure formulation to calculate the objective functions. To validate the proposed optimization procedure, we used 3D printing techniques to create two optimized sandwich panels, and conducted the experimental studies. Results Numerical results demonstrated that the optimized sandwich lattice panel has much improved performance in dynamic and static properties. We also examined the influences of boundary conditions on the topology optimization results. It indicated that the shear stiffness of Pasternak foundation affects the optimization result more obviously than the linear stiffness. Conclusion Numerical and experiment results verified the excellent vibration suppression performance of the optimized sandwich lattice structures. Moreover, the presented optimization procedure shows great potential for the multifunctional design of lattice structures.